2021
DOI: 10.3390/microorganisms9061267
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Metal Ions in Fungal Organic Acid Accumulation

Abstract: Organic acid accumulation is probably the best-known example of primary metabolic overflow. Both bacteria and fungi are capable of producing various organic acids in large amounts under certain conditions, but in terms of productivity-and consequently, of commercial importance-fungal platforms are unparalleled. For high product yield, chemical composition of the growth medium is crucial in providing the necessary conditions, of which the concentrations of four of the first-row transition metal elements, mangan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 83 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…Therefore, the effects of the mRDM medium on 3-HP production were further optimized by alternation of individual components. Maintenance of manganese at a very low concentration (~ 10 ppb) is required to support high-yield production of citric acid in A. niger [ 31 , 45 ] as well as itaconic acid in A. pseudoterreus [ 46 ]. In this study, however, we found that 100-fold higher concentrations of manganese in the culture medium support 3-HP production highlighting the difference in metabolism between production of 3-HP and the organic acids typically produced by these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effects of the mRDM medium on 3-HP production were further optimized by alternation of individual components. Maintenance of manganese at a very low concentration (~ 10 ppb) is required to support high-yield production of citric acid in A. niger [ 31 , 45 ] as well as itaconic acid in A. pseudoterreus [ 46 ]. In this study, however, we found that 100-fold higher concentrations of manganese in the culture medium support 3-HP production highlighting the difference in metabolism between production of 3-HP and the organic acids typically produced by these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, while iron—the most abundant metal in stainless steel—was supplemented here to the growth medium in 0.1 mg L −1 concentration, other citric acid production formulas advocate using up to 1.3 mg L −1 Fe 2+ ions ( Shu and Johnson, 1948b ). Secondly, it is plausible—though not yet confirmed experimentally—that the inhibitory effect of iron in concentrations higher than above on the citric acid yield is actually related to the manganese effect, as even analytical grade iron salts may contain up to 0.5% (w/w) Mn 2+ as impurities ( Karaffa et al, 2021 ). Such Fe/Mn interactions obviously do not exist in our experimental setup.…”
Section: Discussionmentioning
confidence: 99%
“…Specific molar citric acid yields (Y p/s ) are the ratio between the moles of citric acid produced and the moles of D -glucose consumed after the complete depletion of the D -glucose. A high-yield citric acid fermentation (shake-flask or bioreactor alike) was defined as a culture reaching a Y p/s of >0.8 ( Karaffa et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the work on A. oryzae [3,26], three factors were likely responsible for the observed response. These were insoluble solids, metal ions, and pH [13,24,27].…”
Section: Introductionmentioning
confidence: 99%